Improving institutional visibility and reputation in the Open Science era (PUBMET, 2022)
Open Science calls for open access to research results and for more openness and greater transparency in the research process as well. But many institutions lack comprehensive tools to effectively communicate the latter: showcase their rich legacy, available resources, full range of achievements and potential to the wider world.This presentation will cover several tools that are designed to increase the global visibility and reputation of your institution by demonstrating research activities, output, expertise and impact of individual authors and groups. Making this available to the public and professional academic or corporate users facilitates future collaborations.But connecting and managing all the relevant data scattered across multitute of sources on a scale of even mid-size university without a system is impractical, if not impossible. I will focus on the publicfacing side of CRIS/RIM systems and repositories. Additionally I will touch on research data sharing and monitoring tools which is a fast growing topic for a number of institutions.